Primary care ethics: A conversation between a London GP and Milanese GP - Papanikitas, A; Carelli, F (2012)
We present reflections on a conversation by two general practitioners about ethics in primary care. Our aim was to see if we could learn anything by exploring the differences in the framing and enactment of issues seen as 'ethical' between our respective geographies of practice. One of us is a GP in the first five years of practice, who is writing up a qualitative study of ethics in UK general practice. The other is a professor and general practitioner of many years experience. For the purpose of this reflection Professor Francesco Carelli is represented by the initials FC and Dr Andrew Papanikitas by the initials AP. © 2012 Royal College of General Practitioners.